2020
DOI: 10.2217/3dp-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risks of A Widespread Use of 3D Printing for The Manufacturing of Face Masks During the Severe Acute Respiratory Syndrome Coronavirus 2 Pandemic

Abstract: Background: In 2020, the severe acute respiratory syndrome coronavirus 2 pandemic caused serious concerns about the availability of face masks. This paper studies the technical feasibility of user-specific face mask production by 3D printing and the effectiveness of these masks. Material & methods: Six different face mask designs were produced by 3D printing and tested by subjective experimenter evaluation and using a respirator fit testing kit. Results were compared with the requirements as given for stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In five studies of reusable respirators, optimal fit was not achieved [ 46 , 53 , 141 143 ]. Despite the fact that all of the 3D-printed prototypes in the Ballard et al study were built of flexible materials, three of them failed to offer an acceptable fit into the facial dimensions of four individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In five studies of reusable respirators, optimal fit was not achieved [ 46 , 53 , 141 143 ]. Despite the fact that all of the 3D-printed prototypes in the Ballard et al study were built of flexible materials, three of them failed to offer an acceptable fit into the facial dimensions of four individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Duda et al noted that the studied 3D-printed face masks could not be used in clinical settings. The main causes of this are leakages associated with the connection of the masks with the filter material, particularly unwanted leakages brought on by the simplified filter box construction, as well as the low flexibility of the material and the thin sealing line, which prevent the necessary sealing performance on the face [ 46 ]. It is undeniable that the respirators with 3D-printed designs are made of subtle, heavy, and complicated components with different materials, and components’ connections.…”
Section: Resultsmentioning
confidence: 99%
“…5 But Duda et al showed extremely low effectiveness in real-world use of a wider selection of mask designs. 9 These two studies clearly illustrate the need to consider not only the design of AM masks but also the realities and limitations of realworld use.…”
Section: Introductionmentioning
confidence: 98%
“…While there are efforts to produce AM wearables that may provide some level of personal protection, current designs, fabrication choices, and workflows still require progress. Duda et al previously found that the AM face masks they evaluated did not measure up to the particle filtration efficiencies of commercially available FFP2/3 respirators [42] . Chichester et al stated that AM face masks may be able to provide a stopgap measure in crisis condition when traditional N95 masks become unavailable, although cautioned that users should be made aware of their risks and extend of their testing [38] .…”
Section: Introductionmentioning
confidence: 99%